Leptospirosis with Pulseless Electrical Activity (PEA) cardiac arrest in multiple comorbid patient - Amirudin S,; Ismail Mohd Saiboon, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Leptospirosis is one of the endemic diseases in Malaysia. It has a broad spectrum of clinical manifestation ranging from mild illness to life-threatening illness. We report a case of 56-year-old male with multiple comorbidities, who came with history of fever, cough, abdominal pain, vomiting and diarrhea for two days. He presented to the Emergency Department (ED) unresponsive with pulseless electrical activity (PEA). He was resuscitated and achieved return of spontaneous circulation (ROSC) shortly after it. It was complicated with hyperosmolar hyperglycemic state (HHS), oliguric acute kidney injury and non-ST elevation myocardial infarction (NSTEMI). He was then admitted to intensive care unit (ICU) and treated with IV Ceftriaxone 2 g daily for 4 days then was changed to IV Ceftazidime 2 g twice per day for 1 week because of ventilator acquired pneumonia (VAP). His condition improved and was discharge home well after 18 days of admission.